2021
DOI: 10.1101/2021.12.15.472866
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the source of METTL3-independent m6A in mRNA

Abstract: N6-methyladenosine (m6A) is a highly prevalent mRNA modification which promotes degradation of transcripts encoding proteins that have roles in cell development, differentiation, and other pathways. METTL3 is the major methyltransferase that catalyzes the formation of m6A in mRNA. As 30–80% of m6A can remain in mRNA after METTL3 depletion by CRISPR/Cas9-based methods, other enzymes are thought to catalyze a sizable fraction of m6A. Here, we re-examined the source of m6A in the mRNA transcriptome. We characteri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 75 publications
(263 reference statements)
2
9
1
Order By: Relevance
“…Also, we measured relative m6A levels in WT mESC and a Mettl3 knockout mESC line (Figure 3C). M6A levels were reduced over 3-fold in the Mettl3 knockout cell line, which is consistent with the idea that METTL3 is the major m6A methyltransferase for mRNAs in mammals (Poh et al 2021). Furthermore, we found that low technical variability could be achieved when using as little as 25 ng mammalian mRNA (Figure 3C and Supplementary Figure 2).…”
Section: Resultssupporting
confidence: 89%
“…Also, we measured relative m6A levels in WT mESC and a Mettl3 knockout mESC line (Figure 3C). M6A levels were reduced over 3-fold in the Mettl3 knockout cell line, which is consistent with the idea that METTL3 is the major m6A methyltransferase for mRNAs in mammals (Poh et al 2021). Furthermore, we found that low technical variability could be achieved when using as little as 25 ng mammalian mRNA (Figure 3C and Supplementary Figure 2).…”
Section: Resultssupporting
confidence: 89%
“…Our data proved that METTL3 is a critical m 6 A methyltransferase for mouse oogenesis. Although it was reported that METTL3 has been previously reported to be critical for more than 90% of m 6 A marks in mESCs 62 , we detected m 6 A distribution on the mRNAs of the Mettl3 cKO GV oocytes, suggesting the presence of other methyltransferases critical for m 6 A deposition in mouse GV oocytes.…”
Section: Discussioncontrasting
confidence: 84%
“…We therefore prepared total RNA from wild-type mouse embryonic stem (mES) cells as well as Mettl3 knockout mES cells 32 . We used the Mettl3 knockout mES cells generated by Hanna and colleagues, which exhibit a >99% reduction in m 6 A levels in highly purified mRNA 32,33 . Thus, Mettl3 knockout mES cells are an ideal system to establish whether any of the m 6 A signal in the phospho-tag assay derives from mRNA.…”
Section: Resultsmentioning
confidence: 99%